Fostering Religious Tolerance in Early Childhood: The Influence of Parental Role - Pribadi, Imam (Letiges, 2023)
Tolerance is needed in a diverse environment with different religions, ethnicities, customs, and cultures. So tolerance requires a culture that is done from an early age. Religion has fundamental values that teach its adherents to respect people of different faiths and beliefs so that it can be used as a guide for parents to provide assistance and develop tolerance at home. This research aims to investigate how the involvement and role of parents in cultivating the value of patience at home; do they provide support or hinder? The location of this research is Luwu Raya, a fertile area in Indonesia. This is qualitative research where the researchers chose 105 parents who had early childhood and lived together at home. Interviews were conducted via telephone, and several statements and questions were provided via Google form. The research analysis found that most of the early childhood children have parents who are still intact, live together and are given assistance that supports the cultivation of tolerance values at home. The religious-based tolerance values instilled are moderate (tawassuth), tolerant (tasamuh), balanced (tawazun), equality (musawah), peace (islah), and fair (i`tidal). In addition, the role of parents is mainly done by setting an example and, to a lesser extent, by applying rules and respect. This support is also related to the teachings of the Islamic religion, which emphasises the enormous responsibility of parents. The role of parents in cultivating the value of tolerance is a distinctive feature of a Muslim family, which strongly emphasises the solid relationship in parenting between parents and their children. This condition must be continued in school institutions and the environment, dramatically determining these efforts.